Vitamin D status of children with paediatric inflammatory multisystem syndrome temporally associated with severe acute respiratory syndrome coronavirus 2 (PIMS-TS). Issue 6 (28th March 2022) - Darren, Angeline; Osman, Meissa; Masilamani, Kavitha; Habib Ali, Syed; Kanthimathinathan, Hari Krishnan; Chikermane, Ashish; Al-Abadi, Eslam; Welch, Steven B.; Hackett, Scott; Scholefield, Barnaby R.; Uday, Suma; Jyothish, Deepthi
Abstract: Coronavirus disease 2019 (COVID-19) has caused mild illness in children, until the emergence of the novel hyperinflammatory condition paediatric inflammatory multisystem syndrome temporally associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (PIMS-TS). PIMS-TS is thought to be a post-SARS-CoV-2 immune dysregulation with excessive inflammatory cytokine release. We studied 25 hydroxyvitamin D (25OHD) concentrations in children with PIMS-TS, admitted to a tertiary paediatric hospital in the UK, due to its postulated role in cytokine regulation and immune response. Eighteen children (median (range) age 8·9 (0·3-14·6) years, male = 10) met the case definition. The majority were of Black, Asian and Minority Ethnic (BAME) origin (89 %, 16/18). Positive SARS-CoV-2 IgG antibodies were present in 94 % (17/18) and RNA by PCR in 6 % (1/18). Seventy-eight percentage of the cohort were vitamin D deficient (< 30 nmol/l). The mean 25OHD concentration was significantly lower when compared with the population mean from the 2015/16 National Diet and Nutrition Survey (children aged 4–10 years) (24 v . 54 nmol/l (95 % CI −38·6, −19·7); P < 0·001). The paediatric intensive care unit (PICU) group had lower mean 25OHD concentrations compared with the non-PICU group, but this was not statistically significant (19·5 v . 31·9 nmol/l; P = 0·11). The higher susceptibility of BAME children to PIMS-TS and also vitamin D deficiency merits contemplation. Whilst any link between vitamin D deficiency and the severity of COVID-19 and related conditions including PIMS-TS requires further evidence, public health measures to improve vitamin D status of the UK BAME population have been long overdue.